Staff scheduling in restaurants where hall staff and robots cooperate. (7th January 2021) - Tanizaki, Takashi; Shimmura, Takeshi; Fujii, Nobutada; Rene, Antonio Oliveira Nzinga
The number of companies introducing robots as part of their workforce has been increasing in the recent years. One aim of such companies is to have robots perform low value-added work, and humans perform high value-added work. This objective also generally applies to the service industry. Increasing the number of repeat customers and improving profitability are required in the restaurant business. Furthermore, customer satisfaction (CS), employee satisfaction (ES) and management satisfaction (MS) must be simultaneously improved. However, these three indices are in a trade-off relationship. Based on the abovementioned background, this study proposes the modelling of the staff scheduling problem in restaurants to maximise the weighted sum of the CS, ES, and MS values, where hall staff and robots cooperate, as a set covering problem. The simulation results show that increasing the utilisation of robots for low value-added work and hall staff for high value-added work with customer contact contributes to improvements in CS, ES, and MS in restaurants.